Pengaruh Pembiayaan Musyarakah Mudharabah dan Murabahah Terhadap Profitabilitas Bank BSI - Askat Sawaldi; Miftakhus Surur (Dinasti Research, 2024)
This research aims to analyze the influence of musyarakah, mudharabah and murabahah financing on the profitability (ROE) of Bank Syariah Indonesia for the 2013-2023 period. The Ordinary Least Squares (OLS) method was used to analyze the financial data of Bank Syariah Indonesia from 2013 to 2023. The results of the analysis show that the three types of financing, both partially and simultaneously, have a positive and significant effect on the financial performance of Bank Syariah Indonesia. financial performance of Bank Syariah Indonesia. profitability of Indonesian Sharia Bank. These findings underline the importance of effective asset and capital management in improving the financial performance of Islamic banks. Thus, this research provides a better understanding of the relationship between types of sharia financing and bank profitability, as well as providing guidance for sharia bank management in making decisions to achieve better financial performance in the future.